2021
DOI: 10.3892/etm.2021.10034
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of inflammation and oxidative stress in liver cirrhosis

Abstract: Recently, the trend of research has been focused on the role of hematological indicators in assessing the activities of various diseases. The aim of the present study was to determine the usefulness of such hematological indicators for assessment of the relationship between inflammation and oxidative stress in order to provide new predictive tools for a non-invasive investigation of disease outcome for liver cirrhosis patients. A total of 35 subjects with compensated or decompensated liver cirrhosis and 10 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…Many experimental studies have reported that excessive production of ROS in liver damage causes excessive production of proinflammatory cytokines in cells ( Pizzino et al, 2017 ; Pomacu et al, 2021 ). MAPK and NF-κB signaling pathways are activated when cellular stress and ROS production increase ( Hong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental studies have reported that excessive production of ROS in liver damage causes excessive production of proinflammatory cytokines in cells ( Pizzino et al, 2017 ; Pomacu et al, 2021 ). MAPK and NF-κB signaling pathways are activated when cellular stress and ROS production increase ( Hong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that triglycerides play a key role in HSCs activation [ 17 ]. The role of oxidative stress has been reported in various types of liver disease, liver fibrosis, and cirrhosis [ 18 ]. When various etiologies lead to an imbalance between oxidation and antioxidants, both free radicals and oxidative stress products can activate HSCs and eventually lead to liver fibrosis [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of oxidative stress in patients with liver diseases has been investigated. The impact of both ROS and RNS in the liver diseases pathogenesis has been reported (Pomacu et al, 2021). Savu et al, (2012) demonstrated that, plasma TAC was elevated; despite the high levels of oxidative stress, in patients with uncomplicated type2 diabetes compared to that of the control subjects.…”
Section: Pomacu Et Al (2021)mentioning
confidence: 97%